A novel scoring system proposal to guide treatment of dogs with hepatoid gland tumors - Maniscalco, Lorella; Olimpo, Matteo; Parisi, Lorenza; Buracco, Paolo; Mazzone, Eugenio; Martinelli, Greta; Martano, Marina; Iussich, Selina; Morello, Emanuela (Frontiers in Veterinary Science, 2025)
Hepatoid perianal gland tumors are relatively common in dogs, accounting for 25% of all skin tumors. However, the specific factors involved in their development are still not completely clear. It has been established that hormonal influences can impact the formation of these tumors. The prognosis for dogs with perianal tumors depends largely on histology (benign vs. malignant) and, in case of malignancy, it has been suggested that the stage of the disease is important, with a more favorable outcome in dogs having small (under 5 cm in diameter), non-metastatic adenocarcinomas which are surgically removed with non-infiltrated margins. Nevertheless, there is a paucity of studies which thoroughly relate hepatoid gland histotypes to their prognosis; therefore, it is possible that a well-differentiated adenocarcinoma could be misclassified. Based on a retrospective review of 76 dogs with hepatoid gland tumors having clinical follow-up, the aims of this study were (1) to establish a histological grading system capable of potentially predicting prognosis and (2) to explore the role of Ki67 as a potential prognostic marker. Based on histopathological features only, the proposed grading system effectively differentiated tumors with a favorable prognosis from those with a worse prognosis to support histological diagnosis. The evaluation of the Ki67 index was not useful to predict prognosis in this study.